2020
DOI: 10.1111/jocd.13621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the temporal lifting technique using soft tissue fillers

Abstract: Background While the temporal lifting technique has gained increasing attention, there is a dearth of objective and reliable evidence of its effects. Aim The objective of the present study is to analyze the ability of the temporal lifting technique to reduce the midfacial volume by soft tissue repositioning and to achieve an improved pan‐facial appearance by targeting exclusively the subdermal plane of the posterior and superior temple with soft tissue fillers. Methods A total of 12 patients (1 male and 11 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 15 publications
(31 reference statements)
0
42
0
1
Order By: Relevance
“…The latter is most likely related to the postmenopausal hormonal status of these women. 26,[30][31][32][33][34] Sarcopenia is associated with loss in muscle mass (among other things) and would explain the effects observed in our sample of 60 female temples: a reduction in temporal soft tissue volume due to a reduction in temporalis muscle volume and temporal fat atrophy. In males, this effect was not observed despite equal statistical testing and similar sample size; this would support the hypothesis as males are not affected by this hormonal change when using the same statistical cut-off value for age.…”
Section: Discussionmentioning
confidence: 77%
“…The latter is most likely related to the postmenopausal hormonal status of these women. 26,[30][31][32][33][34] Sarcopenia is associated with loss in muscle mass (among other things) and would explain the effects observed in our sample of 60 female temples: a reduction in temporal soft tissue volume due to a reduction in temporalis muscle volume and temporal fat atrophy. In males, this effect was not observed despite equal statistical testing and similar sample size; this would support the hypothesis as males are not affected by this hormonal change when using the same statistical cut-off value for age.…”
Section: Discussionmentioning
confidence: 77%
“…cheek and the jawline: This was showcased in a small sample of Asian patients. 1 In 2020, this hypothesis was confirmed by Hernandez et al 3 in a clinical interventional study treating patients with lateral face soft tissue decent. The results of that independent study revealed that the volume of the lateral midface decreased due to soft tissue repositioning and that the contour of the jawline was more accentuated based on the effects following the subdermal product application of the temple.…”
mentioning
confidence: 84%
“…Procedimientos no quirúrgicos con el uso de hilos y rellenos se han extendido ampliamente en los últimos años, 25,26 aumentando las herramientas disponibles para los clínicos considerando sus ventajas y desventajas; sin embargo, y de la misma forma que ocurre en las investigaciones de orientación quirúrgica, es necesario definir variables de patrón esqueletal de los sujetos de muestra para definir de mejor forma las indicaciones óptimas de tratamiento. En algún punto todas las técnicas pueden ser complementarias, siendo cada vez más necesario definir las mejores opciones para nuestros pacientes (Figura 4).…”
Section: Wwwmedigraphicorgmxunclassified